Causes and Measures of Conflicts among Gang Inmates in Dipolog and Dapitan City Jails - Monceda , Hamilcar S.; Pallega, Rowell; Macaranas, Zoilo J. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Current jail management models strictly prohibit inmates from assisting with jail administration or governance. This is feasible in developed countries where governments can provide adequate resources, security, and personnel. It is not, however, realistic in developing countries like the Philippines, which is characterized by poverty, corruption, and under resourcing of correctional facilities. In such circumstances, inmate leaders tend to share governance with jail administrators. Gang leaders help in maintaining peace and order in jail. This paper explored the causes of conflicts among gang members in Dipolog and Dapitan City jails and identified preventive measures to eliminate threats caused by the conflicts. There were two groups of respondents who were considered in the study. The first group are the gang inmates composed of 188 who answered the survey instrument intended to determine reasons of joining gang and the different causes of conflicts. The second group was the jail personnel who answered the survey instrument on the measures to prevent the conflicts. study revealed that conflicts usually occur during the start and playoff time of National Basketball Association (NBA) and Philippine Basketball Association (PBA) because it is this time that gambling is usually occurred. Conflicts were mainly caused by unpaid debts, theft and overcrowding. Admonition and forfeiture of good conduct time, close confinement and reduction of visiting hours were among the most common measures to discourage conflict. It is recommended to prohibit gambling of any sort. Conduct more physical activities to make the inmates busy.